Nowicjusz w świecie klubu fitness = A Beginner in A Fitness Club Centre - Bazuń, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns on the situation of beginners in a fitness club. Their motivations can be different but their common aim is doing something with their bodies. They want to get fit and be in a good shape or just to spend time nicely training with the others.These people must overcome their shyness and they need to make themselves acquainted with a new situation. The world of fitness contains new places and new people, unknown names of physical exercises, new customs and rituals as well. Beginners quite often must join unknown groups and meet new instructors.
Keywords: fitness; usługi; ciało; kultura popularna; styl życia; service; body; popular culture; life style